Philosophy at the boundary of reason ethics and postmodernity - Bourgeois, Patrick L. (Albany State University of New York Press, 2001)
"In Philosophy at the Boundary of Reason, Patrick Bourgeois clarifies that although deconstruction has much to offer contemporary thinking, it has gone to some philosophical extremes. Taking a cue from this thinking, Bourgeois develops an alternative direction of thought, turning to the position of Paul Ricoeur." "Ricoeur, in the context of recent postmodern deconstruction, has taken into account its positive aspects, but has provided a viable alternative. Ricoeur is one of the best voices within this context today, but accepts an entirely different view of the basic interpretations of meaning, expressing, language, and the living present. In his own critical move beyond Husserlian phenomenology and Heideggerian hermeneutics, and in his efforts to complete the philosophy of Kant on essential points he has not lost their gains, but, rather, has transformed them within a more appropriate ethicomoral philosophy. This investigation puts Ricoeur in his rightful place in the center of contemporary philosophical thinking."--BOOK JACKET.
Ethics at the limit of reason -- Death, end, and limit of philosophy -- Limit, critique, and reason -- Limit and ground in practical reason -- Imagination at the boundary -- Imagination: postmodern deconstruction and ricoeur -- Sign, time, and trace: semiotics and the deconstruction of presence -- Risoeur and Levinas -- Ethics and postmodernity -- The ethics of good, and the morality of obligation -- Judging in concrete situations: the equitable.
Includes bibliographical references and index.
Keywords: Limit (Logic); Philosophy